Temporal changes in treatment selection criteria for skeletal Class III: a comparison of surgical orthodontic and orthodontic camouflage treatments - Yurika Mizoguchi; Chie Tachiki; Yuki Iijima; Dai Ariizumi; Yasushi Nishii; Takashi Takaki; Masae Yamamoto; Akira Katakura (BMC Oral Health, 2026)
Abstract Background Advances in orthodontic treatment mechanics, particularly the introduction of particularly the increasing use of skeletal anchorage, may have altered the boundary between surgical orthodontic and orthodontic camouflage treatments in patients with skeletal Class III. This study explored temporal changes in treatment selection criteria and assessed the diagnostic performance of cephalometric parameters. Methods This study included 160 post-adolescent patients with skeletal Class III treated between 2008 and 2022. Patients were stratified into two periods: P1 (2008–2011) and P2 (2012–2022). In each period, 40 patients from each treatment modality were selected to achieve balanced group sizes after stratification by period and treatment modality. Cephalometric measurements were compared between groups and periods. Receiver operating characteristic (ROC) analysis was conducted for the ANB angle and Wits appraisal. Results In both periods, the surgical group exhibited significantly smaller ANB angles and Wits appraisal values than the camouflage group ( p < 0.05). In the camouflage group, both measurements were significantly smaller in P2 than in P1, suggesting that more severe skeletal Class III cases were increasingly treated without surgery. ROC analysis revealed that Wits appraisal demonstrated greater diagnostic performance than ANB angle (P1: area under the curve (AUC) = 0.904 vs. 0.824; P2: AUC = 0.775 vs. 0.609). The cutoff values shifted from − 1.60° to − 2.65° for the ANB angle and from − 9.50 mm to − 11.50 mm for the Wits appraisal. Conclusions The boundary between surgical and orthodontic camouflage treatments for skeletal Class III has shifted over time, likely reflecting advances in orthodontic treatment mechanics. Wits appraisal demonstrated superior discriminatory ability and is a potentially useful indicator for contemporary treatment decision-making.